THE EFFECT OF PROBLEM-BASED LEARNING MODEL IN INFORMATICS SUBJECTS ON THE CREATIVITY OF STUDENTS IN CLASS X SMK NEGERI 2 TULUNGAGUNG - Hartono, Fabyo Aryasena; Rozi, Fahrur; Sukmana, Farid (STKIP PGRI Tulungagung, 2024)
This research was motivated by the low level of student creativity in the class X informatics subject at SMK Negeri 2 Tulungagung. The purpose of this research is to determine the effect of implementing the Problem Based Learning learning model on the creativity of class X students at SMK Negeri 2 Tulungagung. This type of research is a quasi-experiment with a post-test only control group design. The samples from this research were taken from 2 classes X AKL of SMK Negeri 2 Tulungagung. The experimental class is taught using a problem based learning model and the control class uses a conventional learning model, namely using the discovery learning model. The posttest score results for the experimental class had an average of 86.83 and for the control class the average posttest score was 77.69. Based on the results of the hypothesis test, a sig = 0.000 value was obtained at the significance level = 0.05. This means that the sig value 0.05 means the sig value is outside the H0 acceptance area. So it can be concluded that there is an influence of the problem based learning model in informatics subjects on the creativity of class X students at SMK Negeri 2 Tulungagung